Extensive Thrombectomy as a Legitimate Strategy in Living Donor Liver Transplantation With Advanced Portal Vein Thrombosis. Issue 12 (20th September 2019) - Ikegami, Toru; Yoshizumi, Tomoharu; Tsutsui, Yuriko; Harada, Noboru; Itoh, Shinji; Yoshiya, Shohei; Imai, Daisuke; Uchiyama, Hideaki; Mori, Masaki
Abstract : Management of portal vein thrombosis (PVT), especially advanced PVT involving the superior mesenteric vein (SMV), in living donor liver transplantation (LDLT) is challenging. There were 514 adults who underwent LDLT between 2005 and 2018 included in this retrospective study, and PVT was observed in 67 (13.0%) patients. The LDLT recipients with PVT were characterized by increased portal pressure at laparotomy (26.1 ± 6.0 versus 24.3 ± 5.9 mm Hg; P =  0.03) and at closure (16.8 ± 3.9 versus 15.6 ± 3.6 mm Hg; P =  0.02), increased operative blood loss (14.6 ± 29.7 versus 5.7 ± 6.3 L; P  < 0.01), and decreased 1‐year graft survival (83.5% versus 92.8%; P =  0.04). Among the 18 patients with atrophic or vanished portal vein on pre‐LDLT computed tomography, significant portal atrophy was actually observed only in 1 (5.6%) patient during LDLT surgery. For advanced PVT (n  =  7) involving SMV in era 1, we performed nonanatomical inflow reconstruction using interposition grafts, resulting in significant inflow problems in 4 (57.1%) patients. Thus, for the patients with advanced PVT (n  =  4) in era 2, we abandoned nonanatomical reconstruction and applied extensive thrombectomy under ultrasound guidance with secure shunt ligation, resulting in no inflow problems and no graft loss. In conclusion, even for advanced PVT involving SMV, extensive thrombectomy under sonogram guidance followed by anatomical inflow reconstruction and shunt ligation is a legitimate strategy in adult LDLT with PVT.